1998
DOI: 10.1068/p271357
|View full text |Cite
|
Sign up to set email alerts
|

Cues to Viewing Distance for Stereoscopic Depth Constancy

Abstract: A veridical estimate of viewing distance is required in order to determine the metric structure of objects from binocular stereopsis. One example of a judgment of metric structure, which we used in our experiment, is the apparently circular cylinder task (E B Johnston, 1991 Vision Research 31 1351-1360). Most studies report underconstancy in this task when the stimulus is defined purely by binocular disparities. We examined the effect of two factors on performance: (i) the richness of the cues to viewing dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
5
27
0
Order By: Relevance
“…Our conclusion that relative distance cues affect absolute distance information is consistent with studies showing that estimations of perceived distance under reduced-cue conditions differ from those under full-cue conditions (Glennerster, Rogers, & Bradshaw, 1998;Sedgwick, 1986). Under reduced-cue conditions, an isolated object is typically viewed in total darkness, and the main cues about the object's distance are the absolute distance cues of accommodation and/or vergence (Glennerster et al, 1998;Gogel, 1972).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our conclusion that relative distance cues affect absolute distance information is consistent with studies showing that estimations of perceived distance under reduced-cue conditions differ from those under full-cue conditions (Glennerster, Rogers, & Bradshaw, 1998;Sedgwick, 1986). Under reduced-cue conditions, an isolated object is typically viewed in total darkness, and the main cues about the object's distance are the absolute distance cues of accommodation and/or vergence (Glennerster et al, 1998;Gogel, 1972).…”
Section: Discussionsupporting
confidence: 80%
“…Under reduced-cue conditions, an isolated object is typically viewed in total darkness, and the main cues about the object's distance are the absolute distance cues of accommodation and/or vergence (Glennerster et al, 1998;Gogel, 1972). Under full-cue conditions, objects are typically viewed in an illuminated and structured environment, and, compared with reducedcue conditions,these conditions mainly add visual sources of information about the viewing environment such as relative distance cues (Gogel, 1972;.…”
Section: Discussionmentioning
confidence: 99%
“…The distance cues in the stimulus (e.g. Predebon, 1993;Glennerster et al, 1998) and the task the observer is required to do . Related results in physiology have been reported by Trotter et al (1992) who showed that some cells in area V1 of the monkey modulate their response with changes in viewing distance which suggests that retinal disparity alone may not determine the response characteristics of all the cells underlying disparity processing in the early visual pathway (see also Judge and Cumming, 1986;Erkelens, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence from a 3-D shape perception study that, in a restricted situation where only binocular disparity, accommodation and vergence information was present, the visual system makes shape discrimination errors consistent with mis-estimating viewing distance (Johnston, 1991). Other studies, in which vertical disparity and other information is present (for example see Rogers and Bradshaw, 1993;Glennerster et al, 1998), suggest that in a richer environment, viewing distance can sometimes be obtained veridically. It is likely that in the real world there would be sufficient visual information available to obtain an estimate of object distance, and thus to convert motion estimates from retinal to real-world coordinates.…”
Section: Viewing Distance and Binocular Visionmentioning
confidence: 98%